2017
DOI: 10.1080/08974454.2017.1342745
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Feminist Pathways Perspective beyond the United States: A Profile of Federal Women Prisoners in Argentina

Abstract: World Female Imprisonment List (third edition) Key points * For more details on the figures in this column see Walmsley R. (2015, forthcoming), 'Variations and growth in the levels of female imprisonment', in Women in Prison: the Bangkok Rules and Beyond, proceedings of a colloquium held in Bangkok in March 2014, International Penal and Penitentiary Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
2
8
0
4
Order By: Relevance
“…Nevertheless, some studies have confirmed the roles that economic marginalisation and gender violence play as fundamental issues that contribute to women's offending, especially in the case of drug-related crimes (Antony 2007;Boiteux 2015;CELS 2011;Rodríguez 2005). In a recent study conducted with women who were convicted in a federal jail in Argentina, Salisbury et al (2017) highlighted the high prevalence of victimisation and violence that was evident before criminal involvement, as well as the economic motivation underlying most of the crimes. Regarding gendered pathways, most of the women in federal prisons in Argentina fell into the drug-connected and economic-motivated pathways, while fewer women reported life histories of severe abuse and victimisation.…”
Section: Women's Criminal Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies have confirmed the roles that economic marginalisation and gender violence play as fundamental issues that contribute to women's offending, especially in the case of drug-related crimes (Antony 2007;Boiteux 2015;CELS 2011;Rodríguez 2005). In a recent study conducted with women who were convicted in a federal jail in Argentina, Salisbury et al (2017) highlighted the high prevalence of victimisation and violence that was evident before criminal involvement, as well as the economic motivation underlying most of the crimes. Regarding gendered pathways, most of the women in federal prisons in Argentina fell into the drug-connected and economic-motivated pathways, while fewer women reported life histories of severe abuse and victimisation.…”
Section: Women's Criminal Trajectoriesmentioning
confidence: 99%
“…Although most of our current understanding about offending is based on research conducted among male offenders, a substantial body of research exists that, from the feminist perspective, analyses the distinctive criminal trajectories of female offending and the specific needs of women re-entering society after being incarcerated (Belknap 2007;Brennan et al 2012;Daly 1992;Salisbury et al 2017;Simpson et al 2008). Nevertheless, most of this research has been conducted in anglophone countries, which neglects both the specific historical and societal issues from the global south and the particular ways in which crime has been affected by culture and gender.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies to depart from this was conducted in Argentina by Salisbury et al (2018) to try and fill the gap generated by the lack of studies that focused on the rates of victimization among women offenders in prison. Notably though, this research was published in English.…”
Section: Victimizationmentioning
confidence: 99%
“…No artigo intitulado "Patriarchy as a contextual and gendered pathway to crime: A qualitative study of iranian women offenders", publicado em 2018, os autoresMaghsoudi, Anaraki, e Boostani usaram a Grounded Theory para analisar a história de 23 mulheres que haviam cometido crimes no Iran. Essa teoria foi escolhida com o intuito de entender o tema do ponto de vista das participantes e não dos pesquisadores.Os métodos e abordagens utilizadas por esses pesquisadores permitiram chegar a resultados que identificam fatores para o engajamento de mulheres na criminalidade, experiências comuns presentes nas trajetórias das pesquisadas e efeitos.Grande parte das pesquisas analisadas apontam a presença de vitimização na trajetória das mulheres pesquisadas(KENNEDY;MENNICKE, 2018;GUETA;CHEN, 2016;BECERRA;SERRA, 2017;KÖTTIG, 2016;NUYTIENS;CHRISTIAENS, 2016;SHEPHERD et al;CARR;HANKS, 2013;JEFFRIES;CHUENURAH, 2018;SALISBURY, et al, 2018;SMITH, 2017). Esses trabalhos mostram como as entrevistadas citaram com frequência a ocorrência de violência contra elas perpetrada principalmente pelos pais, companheiros ou pessoas próximas.Na pesquisa de Luz Adriana Aristizábal Becerra e Jenny Cubells Serra (2017), 92% das 94 mulheres entrevistadas presas e ex-presas descreveram terem sido vítimas de violência física.…”
unclassified
“…As autoras concluíram que a vitimização em ambos sexos é um fator que colabora para o comportamento criminal futuro. Elas identificaram ainda questões que merecem ser melhor investigadas como diferentes razões para abandono entre homens e mulheres, a influência de parceiros criminosos e o impacto do encarceramento precoce versus tardio de homens e mulheres.Um estudo realizado no sistema penitenciário argentino(SALISBURY et al, 2018) indicou que aquelas que relataram abuso grave eram mais propensas a serem as que cometeram crimes mais sérios contra pessoas (por exemplo, assalto / agressão, assassinato, sequestro, exploração sexual, escravidão reprodutiva ou remoção de órgãos) em vez de crimes relacionados a ganho financeiro.Além de maus-tratos, a falta de suporte social e disruptura familiar são fatores que aparecem relacionados à criminalidade (MAGHSOUDI et al, 2018). As entrevistas semiestruturadas realizadas…”
unclassified